2022
DOI: 10.1016/j.omtn.2021.11.016
|View full text |Cite
|
Sign up to set email alerts
|

DdCBE mediates efficient and inheritable modifications in mouse mitochondrial genome

Abstract: Critical mutations of mitochondrial DNA (mtDNA) generally lead to maternally inheritable diseases that affect multiple organs and systems; however, it was difficult to alter mtDNA in mammalian cells to intervene in or cure mitochondrial disorders. Recently, the discovery of DddA-derived cytosine base editor (DdCBE) enabled the precise manipulation of mtDNA. To test its feasibility for in vivo use, we selected several sites in mouse mtDNA as DdCBE targets to resemble the human pathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…DdCBEs 1 and zinc finger deaminases (ZFDs) 2 -composed of the split interbacterial toxin DddA tox , a uracil glycosylase inhibitor (UGI), and custom-designed DNA-binding TALE arrays and zinc finger proteins, respectively-are highly versatile genome editing tools that enable targeted C-to-T conversions in the nuclear genome and mitochondrial [2][3][4][5][6][7][8][9] and chloroplast DNA [10][11][12] . DddA tox , an enzymatic moiety in the interbacterial toxin DddA derived from Burkholderia cenocepacia, catalyzes cytosine deamination within double-strand DNA (dsDNA) 13 .…”
mentioning
confidence: 99%
“…DdCBEs 1 and zinc finger deaminases (ZFDs) 2 -composed of the split interbacterial toxin DddA tox , a uracil glycosylase inhibitor (UGI), and custom-designed DNA-binding TALE arrays and zinc finger proteins, respectively-are highly versatile genome editing tools that enable targeted C-to-T conversions in the nuclear genome and mitochondrial [2][3][4][5][6][7][8][9] and chloroplast DNA [10][11][12] . DddA tox , an enzymatic moiety in the interbacterial toxin DddA derived from Burkholderia cenocepacia, catalyzes cytosine deamination within double-strand DNA (dsDNA) 13 .…”
mentioning
confidence: 99%
“…Applying this system to animal mitochondria, it was possible to create mice with base-edited mitochondrial genomes that persisted in a heterochondriomic state and were transmitted through the germline [166,167].…”
Section: Ddda-based Cytosine Base Editors (Ddcbes)mentioning
confidence: 99%
“…These studies prove that the DdCBE platform now allows generation of transgenic animal models for mtDNA disease which have previously been lacking. 26,36 The methodology is ground breaking and has raised high hopes, however, a drawback to the use of the system may arise from unspecificity and off-target effects, as it was soon reported that the mt-DdCBEs lead to off-target effects both in the mitochondrial and nuclear genomes. Low frequency off-target changes in mtDNA seem to be fairly common but even more worrying is the substantial amount of off-target singlenucleotide changes seen in the nuclear genome, 73 which may limit the usability of the mt-DdCBEs at least for therapeutic purposes.…”
Section: Mitochondrial Base Editorsmentioning
confidence: 99%